AB0748 Intermalleolar Distance in Axial Spondyloarthritis: Patients with Psoriatic Spondylitis Have Worse Measurements Compared to Ankylosing Spondylitis. (10th June 2014) - Roussou, E.; Diss, J.; Rajan, N.; Georgiou, A.
Abstract : Background: Ankylosing Spondylitis (AS) disease status is assessed using BASMI [1] which is derived from 5 measures, including intermalleolar distance (IMD), each scored as 0, 1 or 2. Originally, IMD was measured on the floor with the patient supine and knees extended. In practice it is often measured with the patient on a couch. Objectives: To assess whether patient position affected IMD (and its BASMI scoring) in axial-SpA patients by comparing IMD measurements obtained on-the-couch (OC) and on-the-floor (OF). To assess whether there are differences between underlying diseases predominantly AS and Psoriatic arthritis of the AS type (axial PsA). Methods: OC (utilising a 62 cm wide couch) and OF measurements (in duplicate) were attempted on 54 SpA patients (23 male: 31 female) with axial-involvement attending rheumatology clinics. 22 patients had AS and 32 patients had Psoriatic Spondylitis (ax-PsA). Additionally age, gender, height, weight, BMI, and disease duration were also collected. Statistical analyses were performed using unpaired t-tests Results: OC was measured for all patients. Of these 12 (22.2%) resulted in a BASMI-IMD score of 0 (>100 cm; i.e. "mild disease"), 23 (42.6%) scored 1 (70-100 cm; i.e. "moderate disease") and 19 (34.8%) scored 2 (<70 cm, indicating "severe" axial impairment). Importantly, OC-derived IMDs of patients with AS were significantly greater than those with ax-PsA in our study population (87.7±4.0 cm versus 66.7±5.1 cm; p<0.05). Furthermore, markedly more ax-PsA patients had a BASMI score indicative of severe disease: BASMI-IMD score was 2 for 15% AS versus 46.9% ax-PsA patients. Overall, OF measurements were not significantly different from OC measurements in the 45 patients in whom both these values were obtained (78.5±4.0 cm versus 79.3±4.4 cm; p>0.05). Similarly, there was no significant difference between average OC and OF measurements in patients scoring 1 or 2 (i.e. with IMDs <100 cm). In contrast, OC measurements of patients with IMDs >100 cm were 6.1±1.3% less than OF measurements (p<0.05) but only resulted in a change to one AS patient's BASMI-IMD score (from 0 to 1). As for OC-derived IMDs, OF measurements of patients with AS were apparently greater than those with ax-PsA, although this was not significant (90.7±5.8 cm versus 72.1±6.0 cm; p>0.05). Markedly more ax-PsA patients had a "severe disease" OF-derived BASMI scores however: 12.5% AS versus 48.1% ax-PsA patients. There was no significant relationship between IMD (either OC- or OF-derived) and patient age, gender, height, weight, BMI or disease duration. Conclusions: Average BASMI-IMD scores are the same whether the patient is positioned on the floor or on the couch. IMD measurements and BASMI scores are worse in PsA patients with axial disease than in AS patients, probably reflecting greater hip involvement in ax-PsA disease. References: Jenkinson et al. (1994). J Rheumatol 21: 1694-1698. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5987